Modifying the Hydrogenation Activity of Zeolite Beta for Enhancing the Yield and Selectivity for Fuel‐Range Alkanes from Carbon Dioxide. Issue 6 (13th June 2022) - Dokania, Abhay; Ramirez, Adrian; Shterk, Genrikh; Cerrillo, Jose Luis; Gascon, Jorge
Abstract: In order to empower a circular carbon economy for addressing global CO2 emissions, the production of carbon‐neutral fuels is especially desired, since addressing the global fuel demand via this route has the potential to significantly mitigate carbon emissions. In this study, we report a multifunctional catalyst combination consisting of a potassium promoted iron catalyst (Fe−K) and platinum containing zeolite beta (Pt‐beta) which produces an almost entirely paraffinic mixture (up to C10 hydrocarbons) via CO2 hydrogenation in one step. Here, the Fe catalyst is responsible for modified Fischer‐Tropsch synthesis from CO2 while Pt‐beta is instrumental in tuning the product distribution almost entirely towards paraffins (both linear and branched) presumably via a combination of cracking and hydrogenation. The optimal temperature of operation was estimated to be 325 °C for the production of higher paraffins (C5 –C10 ) with a selectivity of ca. 28 % at a CO2 conversion of ca. 31 %. Abstract : In order to fuel a circular carbon economy, catalyst development is required which can directly produce fuels from CO2 . Using potassium promoted iron and platinum modified zeolite beta as components of a multifunctional catalyst, highly selective production of fuel range alkanes is demonstrated via CO2 hydrogenation.